(untitled) (Journal of Mathematics Mechanics and Computer Science, 2010)
In clause the one-dimensional return task of acoustics of definition of acoustic rigidity is considered. The considered ill-posed problem is investigated in operator expression Aq = f, where A – integral operator. The estimation of speed of strong convergence of a method of iterations Landweber is received. The numerical accounts are carried out.